2015
DOI: 10.4161/15384101.2014.980643
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic exchange of TCF3 and TCF4 transcription factors controls MYC expression in colorectal cancer cells

Abstract: Deregulated Wnt/b-catenin signaling promotes colorectal cancer (CRC) by activating expression of the c-MYC protooncogene (MYC). In the nucleus, the b-catenin transcriptional co-activator binds T-cell factor (TCF) transcription factors, and together TCF/b-catenin complexes activate MYC expression through Wnt responsive DNA regulatory elements (WREs). The MYC 3' WRE maps 1.4-kb downstream from the MYC transcription stop site and binds TCF4/b-catenin transcription complexes to activate MYC. However, the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 51 publications
(89 reference statements)
0
44
0
Order By: Relevance
“…In the present study, we found that TCF3 expression was significantly increased in NPC tissues compared to non‐tumourous nasopharyngeal tissues, which suggests that TCF3 is also involved in NPC carcinogenesis. It has been reported that TCF3 overexpression serves as a prognostic marker for judging the survival of patients in several types of human cancers . In this regard, we analysed the relationship between TCF3 staining and the clinicopathological characteristics of the 117 patients with NPC and found a significant correlation between TCF3 expression and clinical stage, locoregional recurrence and distant metastasis.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In the present study, we found that TCF3 expression was significantly increased in NPC tissues compared to non‐tumourous nasopharyngeal tissues, which suggests that TCF3 is also involved in NPC carcinogenesis. It has been reported that TCF3 overexpression serves as a prognostic marker for judging the survival of patients in several types of human cancers . In this regard, we analysed the relationship between TCF3 staining and the clinicopathological characteristics of the 117 patients with NPC and found a significant correlation between TCF3 expression and clinical stage, locoregional recurrence and distant metastasis.…”
Section: Discussionmentioning
confidence: 91%
“…TCF3 plays important roles in embryonic development and regulates the identity and function of epidermal and embryonic stem cells by promoting either stem cell self‐renewal or differentiation depending on the cellular context . Recent studies have demonstrated that TCF3 expression was also closely related to cancer development and progression in several human tumours . However, the role of TCF3 in NPC was not previously addressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the next ranked regulator TCF3 has been found to regulate breast cancer cell differentiation and tumorigenicity [17]. Additionally, previous literature has revealed that TCF3 and TCF4 are overexpressed in rectal cancer and they control MYC expression in colorectal cells [18]. A previous study identified ZEB1 as a key promoter of metastasis in pancreatic and colorectal cancer cells [19].…”
Section: Resultsmentioning
confidence: 99%